2013
DOI: 10.2967/jnumed.112.119289
|View full text |Cite
|
Sign up to set email alerts
|

Textural Features of Pretreatment 18F-FDG PET/CT Images: Prognostic Significance in Patients with Advanced T-Stage Oropharyngeal Squamous Cell Carcinoma

Abstract: Previous studies have shown that total lesion glycolysis (TLG) may serve as a prognostic indicator in oropharyngeal squamous cell carcinoma (OPSCC). We sought to investigate whether the textural features of pretreatment 18 F-FDG PET/CT images can provide any additional prognostic information over TLG and clinical staging in patients with advanced T-stage OPSCC. Methods: We retrospectively analyzed the pretreatment 18 F-FDG PET/CT images of 70 patients with advanced T-stage OPSCC who had completed concurrent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
127
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 39 publications
7
127
0
Order By: Relevance
“…In the first study (Cheng et al, 2013), including 70 oropharyngeal cancers, TLG and texture uniformity were correlated with OS (HR 5.85 and 0.46 respectively). A 3-point risk scale for DFS and OS was proposed, according to the presence of a uniformity ≤ 0.138 and a TLG > 122.9 g. One point was given for each factor.…”
Section: Texture and Shape Analysismentioning
confidence: 99%
“…In the first study (Cheng et al, 2013), including 70 oropharyngeal cancers, TLG and texture uniformity were correlated with OS (HR 5.85 and 0.46 respectively). A 3-point risk scale for DFS and OS was proposed, according to the presence of a uniformity ≤ 0.138 and a TLG > 122.9 g. One point was given for each factor.…”
Section: Texture and Shape Analysismentioning
confidence: 99%
“…The coarseness from NGTDM can be used not only to predict response of chemoradiotherapy for non-small cell lung cancer (10) and esophageal cancer (18) but also to differentiate normal tissues from head and neck tumors and lymph nodes (8). However, it was found to be sensitive to reconstruction settings with a small variation (5% , COV # 10%) over the 4 default reconstruction settings, intermediate variation (10% , COV # 20%) for both impact of iteration number and FWHM, and large variation (COV .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, there are increasing numbers of publications related to the application of TFs in PET tumor imaging, mostly with 18 F-FDG (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These previous studies mainly focused on the predictive and prognostic value (5-10,13-25) of TF and also the potential use in radiotherapy planning (20,21).…”
mentioning
confidence: 99%
“…Radiomic features were also reported as a significant tool to stage cervical cancer based on tumor heterogeneity information 28. Along the same line, Cheng et al29 reported that uniformity, a GLCM feature, might serve as an independent prognostic predictor as well as risk stratification descriptor for patients with oropharyngeal squamous cell carcinoma. Another study investigated the physiologic reproducibility of textural features by characterizing the tumor F18‐FDG uptake heterogeneity in the PET scans of 41 esophageal cancer patients 30…”
Section: Introductionmentioning
confidence: 95%